2022
DOI: 10.1128/aac.01748-21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor-Resistant Mutants Give Important Insights into Candida albicans ABC Transporter Cdr1 Substrate Specificity and Help Elucidate Efflux Pump Inhibition

Abstract: Overexpression of ATP-binding cassette (ABC) transporters is a major cause of drug resistance in fungal pathogens. Milbemycins, enniatin B, beauvericin and FK506 are promising leads for broad-spectrum fungal multidrug efflux pump inhibitors. The characterization of naturally generated inhibitor resistant mutants is a powerful tool to elucidate structure-activity relationships in ABC transporters. We isolated twenty Saccharomyces cerevisiae mutants overexpressing Candida albi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
4
0
2
Order By: Relevance
“…The biochemical function of CauCdr1 was confirmed by determining its ATPase activity and OM sensitivity. The PDR subfamily of ABC transporters is OM sensitive [ 60 ], and previous studies have shown that OM inhibits C. albicans Cdr1 ATPase activity [ 37 , 61 ]. The CauCdr1-6×His ATPase was twice as active as its C. albicans counterpart and showed comparable dose-dependent OM inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical function of CauCdr1 was confirmed by determining its ATPase activity and OM sensitivity. The PDR subfamily of ABC transporters is OM sensitive [ 60 ], and previous studies have shown that OM inhibits C. albicans Cdr1 ATPase activity [ 37 , 61 ]. The CauCdr1-6×His ATPase was twice as active as its C. albicans counterpart and showed comparable dose-dependent OM inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Efflux pump-mediated mechanisms of resistance have also been reported for MGX [ 55 ]. As FK506 is known to inhibit pumps of the ABC transporter family [ 56 ], it will be interesting to see if addition of FK506, even at low concentrations that have no antifungal activity, could further reduce emergence of resistance in culture. These findings could have relevance to the use of fosmanogepix for extended periods in patients with severe fungal infections, who require concomitant immunosuppressive therapy (e.g., hematopoietic stem cell transplant setting).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike human ABC proteins, fungal ABC proteins have a unique domain arrangement of [NBD-TMD]2, with distinctive ELs containing amino acid residues conserved in fungi that are absent from human ABC pumps [ 241 ]. Targeting these ELs with drugs may provide a promising avenue for future antifungal drug development, as they are surface-accessible and not subjected to cellular efflux or detoxification pathways [ 239 , 240 , 241 , 242 ].…”
Section: Biomedical and Therapeutics Applications Based On The Omics ...mentioning
confidence: 99%